Implementation of ASN Core Values BerAKHLAK for Pratama High Leadership Officials in Puncak Jaya Regency, Papua Province - H. Tumiran; Akbar Silo; Yosephina Ohoiwutun; Vince Tebay (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was carried out with the aim of finding out the application of the basic values ​​of ASN BerAKHLAK for Primary High Leadership Officials in Puncak Jaya Regency. This study used descriptive qualitative method. Where data is obtained from interviews, documentation and literature study. Data analysis is carried out through data presentation, data reduction, drawing conclusions and verification. The results of this study show that Pratama High Leadership Officials in Puncak Jaya Regency have implemented the Basic Values ​​of ASN BerAKHLAK mandated by Law Number 5 of 2014 of the State. In the context of implementing the basic values ​​of ASN, it must be carried out with full responsibility, including among high-level pratama officials in Puncak Jaya Regency.